FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP RETURN SAHAM (Study Kasus Perusahaan sektor property & real estate terdaftar di Bursa efek indonesia Periode 2014 - 2017) - Mokhamad Fajar Saputro, 15.05.52.0262; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2019)
This research is a study that analyzes the effect of earning per share, price earning ratio, return on asset return on equity, debt to equity ratio, and current ratio to stock returns in property & real estate companies listed on the Indonesia Stock Exchange in 2014 to 2017. This study uses purposive sampling method in sample selection. Based on the sample criteria, a sample of 152 companies was obtained to 130 during the four-year observation period. The analytical tool used is a multiple linear regression analysis method. The results showed that the variable earning per share have a positive and no significant to the stock return, , price earning ratio have a positif and significiant effect to the stock return, return on asset and return on equity have a positive and no significant to the stock return, debt to equity ratio have negative effect and significant to stock return, and current ratio have a negative and no significant to the stock return.